Developing Digital Media E-Calf As Self-Directed Learning Media For The Fifth Grade Students At Sd Lab Undiksha Singaraja - Gunottama, I.M.A.; Suprianti, G.A.P (Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
This research aimed to develop digital game ‘e-CALF’ as a self-directed learning media in teaching English for fifth-grade students of elementary school. The subject of this research was thirty eight of fifth-grade students in SD Lab UNDIKSHA Singaraja at even semester academic year 2017/2018. This research classified as ‘Research and Development’ (R&D) in which it was adapting the five procedures of ADDIE model by Romiszowski (1996) in Tegeh, Jampel, and Pujawan (2014). Since this research was adapting the ADDIE model, the procedures used were limited until ADD only. The three procedures consist of Analyze, Design, and Development. In conducting the procedures, some instruments were used to operate this research. There interview guide, observation sheet, expert judgment rubric, item of questionnaire, and researcher diary. At the end of this research, there was a prototype product called e-CALF media which was in a form of a digital game. The result of this research is one e-CALF media that was developed based on syllabus competences, syllabus analysis, and also characteristics of media developed based on four topics which are public places, things and transportation, family tree, and describing people. Each topic consists of three types of questions which are vocabulary lists; fill in the blank, and comprehension. In the term of quality, based on the result of expert judgment it was found that e-CALF media was categorized as an excellent media. Furthermore, this media was proper to use for teaching English for fifth-grade students of elementary school